AUDIT PEMBELAJARAN DENGAN E-LEARNING MENGGUNAKAN COBIT 4.1 STUDI KASUS STKIP NAHDLATUL ULAMA KAB TEGAL - Nurkholis . (Indonesian Journal of Informatics and Research, 2020)
The development of technology today cannot be stopped. Many parties take advantage of this technological advancement, one of which is in the learning process or online which is generally known as e-learning as a public service that has been implemented at STKIP NU Tegal which can be accessed through the campus academic website. However, technological advances cannot be avoided from threats or losses so they must be balanced with preventable harm or loss. This study aims to realize the performance of the information system and governance of e-learning learning that has been running. This study uses the COBIT 4.1 framework with the domain of Monitoring and Evaluation and Delivery and Support using the technique of calling the questionnaire data with selected sources according to the domain and Control Objective used. From the research results, it was found that STKIP NU has Elearning management in supporting both online learning services and it is felt that there is a need for improvements to some very important control processes that are related at this time.